2012
DOI: 10.2528/pierc11101202
|View full text |Cite
|
Sign up to set email alerts
|

DESIGN OF MODIFIED 6-18 GHz BALANCED ANTIPODAL VIVALDI ANTENNA

Abstract: Abstract-In this paper, a modified planar balanced Vivaldi antenna with endfire characteristics near the metal surface is proposed for 6-18 GHz applications. The proposed antenna structure consists of three copper layers, among which two external layers locate on the two outsides of two dielectric substrates, and the central layer is sandwiched by these two dielectric substrates. To further enhance the end-fire radiation characteristic, a number of novel techniques are proposed, including elongation and shapin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…In some cases, the directors have been used with higher dielectric constant than that of the antenna substrate to direct most of the energy toward the aperture center [9,10]. However, the improvement on the antenna gain is limited to the frequency band up to 30 GHz [10][11][12][13], with relatively low gain. Another main factor which can be vital in some practical applications, especially in microwave imaging applications, is front-to-back (F-to-B) ratio.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In some cases, the directors have been used with higher dielectric constant than that of the antenna substrate to direct most of the energy toward the aperture center [9,10]. However, the improvement on the antenna gain is limited to the frequency band up to 30 GHz [10][11][12][13], with relatively low gain. Another main factor which can be vital in some practical applications, especially in microwave imaging applications, is front-to-back (F-to-B) ratio.…”
Section: Introductionmentioning
confidence: 97%
“…However, these antennas have low gain in entire band or in some cases at lower Manuscript frequencies [5][6][7][8] as shown in Table I. The dielectric director [9] and lens [10][11][12][13][14] are used to improve the antenna gain, especially at the higher frequencies; their obtained gain values are also summarized in Table I. In some cases, the directors have been used with higher dielectric constant than that of the antenna substrate to direct most of the energy toward the aperture center [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of the performance (fractional bandwidth (BW), maximum size (ρ) and maximum gain (G)) of the designed antennas with Vivaldi and planar monopole antennas described in the literature is presented in Table 1. It is observed that the achieved gain of the SE-APV antenna is much more than that of the antennas presented in [14,15], while maintaining a small size and comparable BW. Similarly, the RGSR antenna achieves higher gain and BW than the UWB antennas proposed in [7,19], while maintaining a comparable size.…”
Section: Antenna Bw ρ (Cm) G (Db)mentioning
confidence: 88%
“…With the Vivaldi antenna, the bandwidth limitation due to the microstrip to slot-line transition can be removed by choosing a proper feed. One solution used in this manuscript is to use a microstrip to stripline or a two-sided slotline transition [13], as recently used by many researchers [14,15]. Thus, no external balun is required to operate with unbalanced transmission lines that are typically used as microwave feed networks [16].…”
Section: Transmitting Antennamentioning
confidence: 99%